Establishing organizational AI governance in healthcare: a case study in Canada - Jee Young Kim; Alifia Hasan; Jacqueline Kueper; Terence Tang; Chris Hayes; Benjamin Fine; Suresh Balu; Mark Sendak (npj Digital Medicine)
Abstract This research applies the People, Process, Technology, and Operations (PPTO) framework to develop AI governance within a large hospital system in Canada that is early in AI adoption. Stakeholder interviews identified the organization’s strengths, gaps, and priorities for AI governance, providing foundational insights into the organization’s readiness and needs. Co-design workshops then adapted the PPTO framework to the organization’s specific context. Together, these efforts led to the creation of policies and the formation of an AI governance committee within the organization. This work demonstrates that the PPTO framework is a practical and adaptable tool for developing AI governance in real-world healthcare settings. It also addresses a critical gap in the field by generating empirical evidence of how a conceptual AI governance framework can be implemented within healthcare delivery organizations to drive organizational change.